Jurisdictional conflict in interfaith child custody disputes: a legal discourse in Malaysian courts - Mohd Zin, Najibah; Mohamed Jani, Hidayati; Hamid, Abdul Ghafur@Khin Maung Sein; Abdul Hak, Nora (International Institute of Islamic Civilisation and Malay World (ISTAC), 2019)
Conflict of jurisdiction between the Civil and Syari’ah court is not a new issue in a dual legal system such as in Malaysia. Intense debate escalates when deciding on custodial rights after divorce in an interfaith marriage. The unilateral conversion to Islam by one party in a non-Muslim marriage has an impact on the status of the marriage and it is a legally recognised ground for divorce. A significant development is when the custody of a child is an issue since both parties are no longer subject to the same set of laws and courts for the purpose of adjudication. The current practice suggests that the converted parent is given preference in custodial rights by the Syari’ah court, which is consistent with the view of the Shafi’i school of law. The approach has caused dissatisfaction particularly among non-Muslim spouses who question whether the decision has served the best interest of the child especially in cases where the child is very young. This paper seeks to examine the extent of the jurisdictional conflict in interfaith custody disputes in Malaysia and the principle applied in the determination of each case. The research method employed in this study is mainly a textual analysis of relevant materials and resolved cases relating to interfaith custody disputes. The study also adopts qualitative analysis in examining the strength and weaknesses of the existing law in resolving the conflicts. Judicial interpretation and the judgments of the court are also analysed in identifying relevant principles adopted by both Civil and Syari’ah courts. The study concludes that of paramount importance is the best interest of the child which must be the guiding principle in deciding custodial rights in interfaith custody disputes, besides other dispute resolution mechanisms.